COVID-19 pandemic and admission rates for and management of acute coronary syndromes in Israel. (14th October 2021) - Asher, E; Fardman, A; Zahger, D; Orvin, K; Mohsen, M; Tsafrir, O; Rubinshtein, R; Jamal, J; Efraim, R; Kofman, N; Halabi, M; Shacham, Y; et al.
Abstract: Background: Since the COVID-19 pandemic outbreak several countries have reported a decrease in the number of patients admitted with non-ST elevation myocardial infarction (NSTEMI). Purpose: We aimed to evaluate admission trend and outcomes of patients with NSTEMI in the COVID-19 era in a nationwide survey. Methods: A prospective, multicenter, observational, nationwide study involving 13 medical centers across Israel. All NSTEMI patients admitted to intensive cardiac care units (ICCUs) over an 8-week period during the COVID-19 outbreak were compare them with NSTEMI patients admitted 2 years earlier (control period) during the Acute Coronary Syndrome Israeli Survey (ACSIS) 2018. Results: There were 624 (43%) NSTEMI patients, of them 349 (56%) hospitalized during the COVID-19 era and 275 (44%) during the control period, representing a 27% increase in NSTEMI admission rate during the COVID-19 era. Approximately 76% were male, median age was 67 years (IQR 58–76). There were no differences in baseline characteristics between the two study periods. During the COVID-19 era, more patients arrived at the hospital via an emergency medical system (EMS) compared with the control period (p for trend = 0.005) Time from symptom onset to hospital admission was longer in the COVID-19 era [687.00 (IQR147–2805) vs. 178.00 (IQR 102- 407), respectively, p-value <0.001]. Nevertheless, time from hospital admission to reperfusion was similar in both groups. Rate of percutaneous coronary intervention was higher in the COVID-19 era group (91.3% vs. 59.7%, respectively, p<0.001). In-hospital mortality rate was similar in both groups (2.3% vs. 4.7%, respectively, p=0.149) as was the 30-day mortality rate (3.7% vs. 5.1%, respectively, p=0.238). Conclusions: In contrast to previous reports, in Israel, admission rate of NSTEMI was increased during the COVID-19 era. With longer time from symptoms to admission, but with the same time from hospital admission to reperfusion therapy and with similar in-hospital and 30-day mortality rates. Funding Acknowledgement: Type of funding sources: None.